PENDAMPINGAN SERTIFIKASI HALAL GRATIS (SEHATI) UNTUK USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI DESA SUKAMUKTI - Putra, Purnama; Fadhliah, Syifa; Khoiriyah, Ummi (DEVOSI, 2024)
Halal certification is an obligation for MSME players in Indonesia. In accordance with government directives in Government Regulation Number 39 of 2021 which requires MSMEs to have halal certification from 17 October 2019 to 17 October 2024. After 17 October 2024, actors who do not have halal certification will receive sanctions from the government. The problem that occurs in the community related to the small number of MSMEs that carry out halal certification is the lack of knowledge and information regarding the process and flow of applying for halal certification for MSMEs, making MSMEs unable to carry out halal certification. The implementation of this community service was carried out in Sukamukti Village by holding a socialisation and assistance program for Free Halal Certification (SEHATI) for MSMEs in Sukamukti Village. The method of implementing this activity uses a training method to introduce new things to the community followed by the implementation of halal certification assistance. The conclusion in this mentoring activity runs smoothly. Overall, MSMEs that can be certified halal are Warung Seblak which focuses on food through a self-declaration programme. Halal certification shows positive results, including having an impact on increasing partner turnover.